A short history of myth. - Armstrong, Karen, 1944- (New York Canongate, 2005)
Human beings have always been mythmakers. Theologian Armstrong here investigates myth: what it is, how it has evolved, and why we still so desperately need it. She takes us from the Paleolithic period and the myths of the hunters, up to the Great Western Transformation of the last five hundred years and the discrediting of myth by science. The history of myth is the history of humanity, our stories and beliefs, our curiosity and attempts to understand the world, which link us to our ancestors and each other--From publisher description.
What is a myth? -- Palaeolithic Period : Mythology of the hunters (c. 20000 to 8000 BCE) -- Neolithic Period : Mythology of the farmers (c. 8000 to 4000 BCD) -- Early civilisations (c. 4000 to 800 BCE) -- Axial Age (c. 800 to 200 BCE) -- Post-Axial Period (c. 200 BCE to c. 1500 CE) -- Great Western Transformation (c. 1500 to 2000).
Keywords: Myth -- History; 291.13 -- Mythe. Vergelijkende mythologie